A new meshfree approach for vibration analysis of arbitrary restrained laminated composite cylindrical shell under thermal environment. (July 2022) - Zuo, Peng; Shi, Xianjie; Ge, Renwei; Luo, Jingrun; Ning, Minliang
Abstract: This study presents a new meshfree approach for thermal vibration analysis of laminated composite cylindrical shell subject to arbitrary boundary conditions. The boundaries of laminated structures are constrained by artificial springs with variable stiffness. The spectro-geometric method (SGM) combined sine/consine functions containing circumferential wavenumber is employed to expand the displacement components of physical system. Following Reissner-Naghdi's thin shell theory, the Lagrangian energy functionals of the studied structure is derived, and the governing equation of laminated composite cylindrical shell under thermal environment is formulated with Rayleigh-Ritz method. After that, the convergence investigation and accuracy examination of the present method are both carried out by performing some numerical case studies. Finally, the effect of some crucial factors including temperature variable, boundary condition, length-radius ratio and laminated layers on the thermal vibration characteristics of laminated composite cylindrical shell are also studied.